2015
DOI: 10.1068/p7811
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Red on the Road

Abstract: Human and animal research has found that red perception is associated with specific behavioral reactions, generally characterized by intense responses. Here, we explored whether red cars are perceived as more dangerous than other colored cars. One hundred Spanish drivers examined several road scenarios which involved hazardous cars with different colors: red, green, yellow, black, gray, and white. Driver's behavior (response time and probability of braking) and the perceived level of risk for each scenario wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The pilot-study results suggested that the road-crossing behavior varied with the vehicle, which motivated us to investigate if the brightness was the cause. A recent study by Díaz-Román et al. (2015), who used a computer simulator, further supported the same hypothesis.…”
Section: Motivationmentioning
confidence: 67%
See 1 more Smart Citation
“…The pilot-study results suggested that the road-crossing behavior varied with the vehicle, which motivated us to investigate if the brightness was the cause. A recent study by Díaz-Román et al. (2015), who used a computer simulator, further supported the same hypothesis.…”
Section: Motivationmentioning
confidence: 67%
“…The pilot-study results suggested that the road-crossing behavior varied with the vehicle, which motivated us to investigate if the brightness was the cause. A recent study by D ıaz-Roma´n et al (2015), who used a computer simulator, further supported the same hypothesis. They reported that participants reacted significantly earlier to black than to white vehicles in various hazardous vehicle-vehicle encounters.…”
mentioning
confidence: 67%
“…Previous studies addressing the effect of color on psychological functioning have mainly focused on the color red, showing that red heightens attention (Díaz-Román et al, 2015; Pravossoudovitch, Cury, Young, & Elliot, 2014), undermines performance (Shi, Zhang, & Jiang, 2015), increases aggressiveness and dominance (Bagchi & Cheema, 2013; Fetterman, Liu, & Robinson, 2015; Krenn, 2014), and enhances attraction (Elliot & Niesta, 2008), dependent on its context (see Elliot & Maier, 2014, for a review). It has been suggested that many of these effects are the result of learned color associations.…”
Section: Discussionmentioning
confidence: 99%